Domestic Electricity Consumption and the Public Awareness Factor - Georgiou, Avraam; Ioannou, Petros; Christodoulides, Paul (My University, 2013)
Access to energy and in particular electricity is viewed as a fundamental right of every household. The accessible source of electricity gets distributed to different electrical loads within the household without people being aware of the individual consumption per load, due to the fact that the overall cost is reported as a single number in the electricity bill. In this study we investigated the awareness and knowledge of household consumers with regard to issues associated with electricity consumption and cost. As a first stage, a sample of 300 households all around Cyprus was randomly selected in January 2010. The occupants were asked to provide relevant information about their household as well as answer some survey questions associated with knowledge of electricity consumption. The survey demonstrated clearly that most people are not aware of electricity consumption and cost, indicating a potential for reducing unnecessary consumption. The second stage was the installation of 50 smart monitors, one per household, with a small display indicating the cost of electricity consumed per hour. The monitor enabled the occupants of the household to identify the cost for appliances, lighting and so forth, by observing the change in the displayed cost when the load was switched on. The device became an effective educational tool that motivated the users to be more alert in switching off unnecessary loads. The third stage consists of monitoring the consumption of each of the 50 households over a 2 year period 1 year prior to the use of the monitoring device and 1 after. The results so far demonstrate clearly that the information provided by the device led to changes in the use of electrical loads that resulted in an average of 25% savings ranging from a minimum of 10% to a maximum of just over 40%. The study of the 50 households helped to identify some common areas of savings which were verbally communicated to the remaining 250 households participating in the project but did not have access to a monitoring device. In those cases the average savings were about 10%. The study clearly demonstrates that saving electrical energy has a lot to do with education and awareness regarding costs of different electrical loads. The use of a smart device that allows people to observe cost changes for different loads seems to be much more effective than booklets and verbal suggestions regarding energy savings. In a future study, the analysis of a statistical model on the profile of the average Cypriot household will be attempted. Features like education, financial status, age and other important factors will be tested against different ways of informing and educating people in changing their habits on electricity consumption.
Keywords: Energy saving; Real time information; Monitoring system; Smart meter